A mini-review of thiourea-based polymers in catalysis: from hydrogen-bonding to emerging polymerization strategies - Ros Azlinawati, Ramli; Bohari, Mohd. Yamin (Wiley, 2026)
Thiourea derivatives are powerful hydrogen- bond donors that have revolutionized small- molecule catalysis, but their integration into polymer frameworks remains comparatively underexplored. Thiourea- based polymers offer unique advantages, including tunable architectures, enhanced stability, and recyclability, but challenges in synthesis, functional stability, and active- site distribution hinder wider application. This mini- review critically highlights advances from hydrogen- bonding catalysis to emerging polymerization and post- functionalization strategies, identifies key research gaps, and outlines opportunities for designing multifunctional catalytic polymers. By bridging molecular thiourea chemistry with macromolecular design, this review provides a timely perspective to guide sustainable catalysis and expand the role of thioureas in polymer science.